Jakościowa i ilościowa analiza słownictwa oraz jednostek quasi- i nieleksykalnych wypowiedzi w dialogach zadaniowych „origami” - Szczyszek, Michał; Karpiński, Maciej (Investigationes Linguisticae, 2010)
In this text, an analysis of the lexical material obtained from the recordings of Polish task-oriented dialogues is presented. Some findings regarding quasi- and non-lexical units are also mentioned. The dialogue task involved the reconstruction of a figure made of paper. It was carried out in two settings: Mutual visibility and limited visibility. The analyses of the vocabulary are focused on finding its specific features and the differences between the structures of the vocabularies of instruction givers and instruction followers in the two settings. Frequency lists as well as most frequent bigrams extracted from the material are discussed in terms of their relatedness to the settings, the roles of the speakers and some other factors.